Model Fintech Syariah Berbasis Edukasi dan Securities Crowdfunding untuk Meningkatkan Literasi dan Inklusi Keuangan - Muhammad Ramdan Ridwanullah; Ganis Khairulysa Prasetiyo; Sela Nur Aulia; Joni Joni; Raihani Fauziah (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
Sharia based financial technology (fintech) that integrates educational features and securities crowdfunding is considered a strategic approach to address the low levels of Islamic financial literacy and inclusion in Indonesia. This article aims to examine how the integration of Islamic financial education and the use of sharia-compliant securities crowdfunding platforms can serve as an effective model to enhance public participation especially among MSMEs and younger demographics in the Islamic financial ecosystem. The study employs a literature review and case analysis based on recent scholarly works and industry reports. Findings indicate that fintech platforms equipped with interactive financial education modules and sharia investment simulations can significantly improve public understanding of Islamic financial principles and products. Moreover, sharia-based securities crowdfunding offers participatory investment opportunities while promoting ethical and halal economic activities. Nonetheless, challenges remain in regulatory alignment, sharia compliance verification, and public trust. Therefore, collaboration among regulators, industry players, and educational institutions is essential to foster an inclusive, transparent, and sustainable Islamic fintech ecosystem. This model is expected to be an innovative solution to expand access to Islamic financial services while strengthening public literacy and confidence in Islamic finance.